STRENGTHENING FINANCIAL TECHNOLOGY REGULATION TO EMPOWERMENT FINANCIAL INCLUSIVE - Lastuti Abubakar; Tri Handayani (Diponegoro Law Review, 2019)
After the global crisis at 2008; Financial Inclusion became a focus in many international forums including developing countries and Indonesia. Refers to international best practice, the solution is made: the national financial inclusion strategies that conducted among other things such as launch a certain programs such as branchless banking and peer to peer lending are the solutions has made.  One of the financial inclusive principles is technological innovation to expand public access using financial technology to reach financial systems. This research aims to study and analyze fintech regulation in Indonesia to empower the financial inclusive. Research method is used a normative juridical and descriptive analytics specification. Data has analyzed in a qualitative juridical. The results showed that Fintech has a role in broaden the access for community to financial systems so that it can be a tool for poverty alleviation and economic equality. Likewise, to strengthening and rearrange Fintech regulation is needed due to overcome the obstacles such as the misuse of personal data, the growth of shadow economy and consumer losses. Therefore, it is required a comprehensive regulation, cooperation between authorities and institutions in order that Fintech can be optimally empower the financial inclusion.